Molecular mechanism, diagnosis, and treatment of VACTERL association - Sun, Manluan; Zhao, Qiyu; Yang, Bingyu; Liu, Lili; Zhou, Caiquan; Yao, Xinbo; Bu, Jia; Bian, Jiang; Ge, Sai; Zhu, Zhuangyan; Liu, Binyu (Frontiers in Pediatrics, 2025)
The VACTERL association is a non-random cluster of congenital malformations involving six distinct conditions: vertebral defects (V), anal atresia (A), cardiac defects (C), tracheoesophageal malformation (TE), renal defects (R), and limb anomalies (L), and is diagnosed when a fetus exhibits three or more of these. Its prevalence is approximately 0.47–0.58 per 10,000 live births. This paper examines the effect of disruptions in the Sonic Hedgehog and cilia-associated signaling pathways, genetically related developmental variations, and maternal environmental factors on the development of VACTERL. In the SHH signaling pathway, we focus on the effects of Sonic Hedgehog ligands, GLI transcription factors, and factors influencing GLI activity (RAC1 and ZIC3), as well as downstream targets (FOXF1 and HOXD13) and other genes and proteins involved in the regulation of SHH signaling (FGF8 and LPP), in the pathogenesis of VACTERL. In this context, ZIC3, which was shown to play a major role in VACTERL pathogenesis in large-scale resequencing, and TRAP1, which was associated with VACTERL pathogenesis in whole-exome resequencing, were highlighted. We also examine the cilia-associated signaling pathways, particularly the role of IFT172 and candidate ciliopathy genes. In addition, we describe the influence of TRAP1, COL11A2, SALL4, WBP11, Copy Number Variants, and maternal environmental factors on VACTERL. We also discuss current diagnostic, therapeutic, and prognostic approaches including prenatal and postnatal treatment options. Furthermore, we highlight the advantages of thoracoscopic surgery over traditional open-surgical treatment while discussing the differential diagnosis of VACTERL from other neonatal malformations with similar symptoms, such as Townes-Brocks syndrome, Baller-Gerold syndrome, and CHARGE syndrome.